Risk factors for pathological fracture in patients with mandibular osteoradionecrosis - Hiroaki Ohori; Eiji Iwata; Daisuke Takeda; Junya Kusumoto; Takumi Hasegawa; Masaya Akashi (Scientific Reports, 2023)
Abstract Osteoradionecrosis (ORN) often results in pathological fractures through progression. We aimed to identify the risk factors for pathological fracture in patients with mandibular ORN. Seventy-four patients with mandibular ORN were included in this retrospective study. We investigated various risk factors for pathological fracture in patients with mandibular ORN, including number of mandibular teeth with a poor prognosis each at initial evaluation before radiation therapy (RT) and when fracture occurred, and the proportion of antibiotic administration period in a follow-up duration after RT. The rate of occurrence of pathological fractures in patients with mandibular ORN was 25.7%. The median of duration between RT completion and fracture occurrence was 74.0 months. We found that pathological fracture was significantly associated with a larger number of mandibular teeth with a poor prognosis at initial evaluation before RT (P = 0.024) and when fracture occurred (P = 0.009). Especially, a larger number of mandibular teeth with P4 periodontitis, in other words severe periodontal status, was related to pathological fracture in both timings. The proportion of antibiotic administration period in a follow-up duration was also significant risk factor (P = 0.002). Multivariate analyses showed statistically significant associations between pathological fracture and a larger number of mandibular teeth with a poor prognosis when fracture occurred (hazard ratio 3.669). The patient with a larger number of mandibular teeth with P4 periodontitis may have a risk of not only occurrence of ORN but resulting in pathological fracture by accumulation of infection. Surgeons should consider extraction of those teeth regardless of before/after RT if necessary for infection control.